Quem são "todos"?: Investigando o perfil dos grupos brasileiros de Ginástica para Todos - Raffi Menegaldo, Fernanda (2024)
This study aimed to identify the profile of Brazilian Gymnastics for All (GfA) groups. Quantitative research was carried out using an online questionnaire (Google Forms) answered by 378 adult members from 22 GfA groups. Data analysis was made using Descriptive Statistics. The data confirm the protagonism of the Southeast region, as well as confirming the strong role of public universities in the GfA development in the Brazilian context. There is a predominance of female participants in the composition of the groups, although in extension projects this difference is lowered. Regarding the age of participants, adherence to the GfA activities by different age groups was confirmed, even within the same group, but with a significant predominance of young adults. Finally, the data also support the hypothesis that GfA can be practiced as a long-term physical activity, as more than a third of the members report being part of their respective groups for over four years.